Rate of Positive Family History in Iraqi Patients with Breast Cancer - Alabedi , Haydar; Khalil , Nooruldeen Suhail; Dawood , Muammel Safaa; Mejbel , Yasameen Ali; Alazawy , Nabaa (Journal of Contemporary Medical Sciences, 2025)
Objective: The objective of this study was to understand the effect of positive family history as a risk factor between breast cancer patients depending on clinical and pathological features. Methods: This is a clinical survey study contained 507 Iraqi breast cancer patients from July 2022 to May 2023. The assessment of patients performed using histopathological examination of tissue samples from breast biopsy or surgical excision. Family history interviews recorded. Participants were recruited from various healthcare facilities. The questionnaire covered age, residency, family history, metastasis, and the specific site of breast cancer. A signed informed consent process ensured patient confidentiality. Results: This study examined the characteristics of breast cancer patients, including sex, age group, geographic distribution, and laterality. The sample consisted of 507 confirmed cases, 99.8% of which were females. Most patients were diagnosed on the left side, with 253 (49.9%) and 227 (44.77%) diagnosed on the right side. Unilateral breast cancer was predominant, with 53% of patients having bilateral breast cancer. Among the 507 patients, 31.76% had a positive family history of breast cancer, whereas 68% had a negative family history. Most patients had a first-degree relative to positive cancer, with 58 (36.02%) having a first-degree relative to positive cancer. The majority of cases did not show metastatic features, with the most metastatic cases being spread to the lymph nodes (6.7%). Conclusion: The majority of breast cancer cases were left-sided, with 31.7% having a positive family history and 68% having a negative one. Most cases had a second-degree relative to a positive cancer history, with most cases spreading to the lymph nodes.